Depression and prevention during the COVID-19 pandemic - Widiyanto, Juli; Putri, Silvia Elki (MEDISAINS, 2022)
The impact of the COVID-19 pandemic affects all aspects, namely aspects of health, economy, education, and social life. Depression is a problem that everyone is at risk of experiencing during the COVID-19 pandemic. The condition of depression dramatically affects quality and productivity, primarily if it occurs at a productive age. Depression requires primary, secondary, and tertiary prevention at individual, family, group, and community levels.